(untitled) (Actualizaciones en Sida e Infectología, 2025)
Introduction: Antimicrobial Stewardship Programs (ASP) use evidence-based flowcharts to standardize infection management. Their implementation is rarely evaluated, limiting the validation of their impact. Objective: To evaluate the adequacy of antibiotic treatment according to the ASP flowchart in patients with community-acquired pneumonia (CAP) hospitalized in a moderate care unit at a tertiary care center. Methods: Observational, retrospective study (April-December 2024) was conducted on 50 immunocompetent patients ≥18 years of age with CAP hospitalized in a moderate care unit. Six adequacy indicators were analyzed (empirical selection, dosage, time to first dose < 4 hours, therapeutic adjustment, sequential therapy, and treatment duration), classified as optimal (>90%), intermediate (60-90%), or low (<60%). Results were expressed using descriptive statistics. Results: The mean age was 74.8 years, and 56% were male. Adequacy was low for four indicators: empirical selection (48%), therapeutic adjustment (23%), sequential therapy (55%), and treatment duration (16%). The time to first dose < 4 hours was appropriate at an intermediate level (66%). Correct dosage (96%) was the only indicator that reached an optimal level. Discussion: There are critical gaps in the antibiotic treatment adequacy in NAC associated with low adequacy of empirical antibiotic treatment and adjustment, delay and underuse of sequential therapy, and excessively prolonged treatments. Immediate interventions from the ASP Team are needed, focusing on training in empirical selection and therapeutic adjustment, mandatory reassessment protocols to counteract therapeutic inertia, support systems for sequential therapy and duration, and prospective audits with real-time feedback.